Partner prenatal care and paternal presence during pregnancy: perceptions of fathers and health professionals - Sales Rodrigues, Marcos Antônio; Alves Moreira, Katia Fernanda; Evangelista Rodrigues Fernandes, Daiana; Petean Parmejiani, Ellen; Macedo Cordeiro Figueiredo, Edilene (Estação Científica, 2025)
This study explores how fathers/partners and healthcare professionals from a family health team in Xxxxxxx perceive men’s involvement in prenatal care. Conducted between March and June 2023, this qualitative, exploratory study used semi-structured interviews, analyzed via Bardin's content analysis. Three themes emerged: (1) challenges in healthcare access, (2) men's experience during pregnancy and caregiving, and (3) the significance of prenatal care for fathers/partners. While most partners recognize the importance of male participation in caregiving, traditional views persist among some fathers and professionals, who see men as primarily providers, seeking healthcare only when ill. Prenatal care remains largely viewed as a woman’s responsibility, with men's involvement often undervalued by healthcare professionals, who overlook its potential to promote men's health and improve their access to services.